A multicenter, phase I/II trial of biweekly S-1, leucovorin, oxaliplatin and gemcitabine in metastatic pancreatic adenocarcinoma–TCOG T1211 study. (January 2020) - Chiang, Nai-Jung; Tsai, Kelvin K.; Hsiao, Chin-Fu; Yang, Shih-Hung; Hsiao, Hui-Hua; Shen, Wen-Chi; Hsu, Chiun; Lin, Yu-Lin; Chen, Jen-Shi; Shan, Yan-Shen; Chen, Li-Tzong
Abstract: Background: This phase I/II study evaluated the feasibility and efficacy of S-1, leucovorin, oxaliplatin and gemcitabine (SLOG), a triplet regimen, for treating patients with metastatic pancreatic ductal adenocarcinoma (PDAC). Methods: Patients with chemo-naive, metastatic PDAC were eligible to receive fixed-rate infusion (10 mg/m 2 /min) of gemcitabine of 800 mg/m 2 followed by oxaliplatin of 85 mg/m 2 on day 1 plus oral S-1 and leucovorin (20 mg/m 2 ) twice daily from days 1 to 7 in a 2-week cycle. The dose of S-1 would be escalated from 20, 30, 35 to 40 mg/m2 in a 3 + 3 designed phase I part to determine the maximum tolerated dose (MTD) for phase II study, in which the primary end-point was objective response rate (ORR). The recommended dose of S-1 was from phase I. This trial is registered at ClinicalTrials.gov: NCT01415713 . Results: Seventy-three patients were enrolled. In the phase I study (n = 19), the MTD of S-1 was 35 mg/m 2 twice daily. Of 54 patients in phase II, the ORR was 40.7% (95% confidence interval [CI], 28%–55%). The median progression-free survival and overall survival were 7.6 (95% CI, 5.6–11.0) and 11.4 (95% CI, 8.1–16.3) months, respectively. The most common grade III/IV adverse event was neutropenia (40.7%). Twenty-four percent of patients had SLOG treatment for more than 1 year. The mean relative dose intensities of gemcitabine, oxaliplatin, and S-1 were 92%, 92% and 89%, respectively. Conclusion: Biweekly SLOG is a feasible regimen with promising activity and safety profiles. A randomised study comparing SLOG versus modified folinic acid, fluorouracil, irinotecan, and oxaliplatin (FOLFIRINOX) in advanced PDAC is ongoing (ClinicalTrials.gov: NCT03443492 ). Highlights: Systemic chemotherapy is the standard of care for patients with unresectable advanced or metastatic pancreatic cancer. The maximum tolerated dose of the SLOG regimen, S-1 plus leucovorin in combination with gemcitabine and oxaliplatin has been defined. SLOG showed promising efficacies and favourable safety profiles in patients with metastatic pancreatic cancer. A randomised phase II trial comparing SLOG versus modified FOLFIRINOX in advanced pancreatic cancer is ongoing.